Role, function, and competency requirements for a successful BIM implementation (2019)
"Thus far, it's not clear whether a new role must be defined in the companies or if the existing workforce could acquire new capabilities that enable them to successfully implement BIM. This decision may prove itself crucial to the success or failure of a project and the adoption of BIM and new technologies in construction industries. It is precisely that question that this paper aims to answer, should companies train their current work force or hire new BIM specialized works in order to achieve a successful BIM implementation?"--Tomado del Formato de Documento de Grado.